Distant Metastasis in Carcinoma Oral Cavity: Incidence and Prognostic Factors - Kalyani, Nikhil; Bhosale, Bharat; Singh, Shambhavi; Tarafdar, Debayan; Katna, Rakesh (Indian Journal of Medical and Paediatric Oncology, 2021)
Aim The predominant pattern of failure for oral carcinoma is locoregional failure. With improvement in locoregional control, incidence of distant metastasis has increased. Reported incidence of distant metastasis is 8 to 10%. With an aim to define incidence and predictive factors for distant metastasis posttreatment of oral cavity cancer, the present analysis was done.Materials and Methods This is a retrospective chart review of 531 patients who underwent surgery for oral cavity carcinoma from August 2013 to December 2017. All patients had undergone surgery followed by adjuvant treatment as per histopathology report.Results The median age of the cohort was 49 years. The median follow-up of alive patients was 21 months (range: 1–56 months). Locoregional recurrence seen in 61, distant metastasis in 23, and 72 patients had locoregional recurrence with distant metastasis. Total incidence of distant metastasis was 18% (95 patients) with median detection 7 months’ posttreatment. The sites of distant metastasis were: lung in 49 patients, bone in 9 patients, and multiple sites in 37 patients. Nodal stage (N2 and N3), differentiation, young age, and perineural invasion were associated with higher incidence of distant metastasis on multivariate analysis.Conclusion The incidence of distant metastasis was found to be higher as compared with published literature. Possibility of adjuvant systemic therapy may be explored in future studies.
Keywords: carcinoma oral cavity; differentiation; distant metastasis; nodal stage; PNI